Jungle cruise [videorecording (DVD)] - Johnson, Dwayne, 1972-; Blunt, Emily; Ramírez, Édgar, 1977-; Plemons, Jesse, 1988-; Giamatti, Paul (Disney, 2021)
Her funding rejected by the Royal Society, and pursued by an obsessed member of German nobility, Lily travels from London to the Amazon jungle and enlists Frank's questionable services to guide her downriver in search of an ancient tree with unparalleled healing abilities which would change the future of medicine. Thinking she sees Frank for who he truly is -- a pun-loving con man who embellishes danger on his tours in order to get better tips from his customers -- Lily can't stand the boatman, but as they spend time together on their journey, the unbelievable truth about Frank may be exactly the thing which guides her to her goal.